Deciphering the student dilemma: The quest for passion and purpose on addmision of tadris biology department a religious higher education institutions - Elfianti, Maya; Ferry, Dharma; Damni, Albertos (Jurnal Pijar Mipa, 2023)
The primary objective of this study is to scrutinize the underlying factors that inform students' choices when selecting the Tadris Biology major at a Religious Higher Education Institution located in Jambi. The research adopts a qualitative, remarkably grounded theory approach as its methodological framework. The central aim is to comprehensively examine the justifications and rationales that steer students toward their decision to pursue the Tadris Biology major. The research methodology is firmly anchored in qualitative paradigms, and grounded theory provides the overarching structure for this investigation. The data collection technique in this research is by using a questionnaire. Data analysis is systematically carried out through thematic analysis, allowing for extracting key themes and insights. The sample selection process is methodically executed, utilizing the theoretical sampling method. The samples were 98 students registered in the Tadris Biology department at an Islamic college. The research findings collectively underscore the significant influence of Gender-Based Considerations, Parental and Familial Influence, Personal Interest in Biology as a Major Field of Study, an Exploration into the Impact of School Background, and Prospects for Future Careers in steering students' decisions within this academic domain.